2006
DOI: 10.1021/ma0606760
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Amplification of Macromolecular Helicity in a Lyotropic Liquid Crystalline Charged Poly(phenylacetylene) by Nonracemic Dopants in Water and Its Helical Structure

Abstract: We report a unique hierarchical amplification of chiral information from a nonracemic guest to macromolecular helicity, followed by a mesoscopic, supramolecular cholesteric twist in water. This remarkable chiral amplification involves two-step chirality transfer processes, which enable the detection and sensing of an extremely small imbalance in chiral guest molecules. The macromolecular helicity with an excess single-handed helix was first induced in the positively charged, chromophoric poly(phenylacetylene),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 67 publications
6
99
0
Order By: Relevance
“…If the solution contains enantiomeric or diastereomeric right-and left-handed helices, q c also depends on the excess of the one helical sense. 15,16,18 Under the constant copolymer concentration of 15 wt% in benzene at B25 1C, the q c value of poly(1L m -co-1D n ) was found to increase with the increasing percentage ee of the copolymer components, where a larger q c value means an increased preference of the one-handedness, and the copolymers with 30-50% ee of the components showed as large a q c value as that of the homopolymer poly-1L (100% ee; Figure 2C). This remarkable increase in the q c value against the percentage ee of the copolymers (positive nonlinear effect) indicated a significant amplification of the helical-sense excess in the LC state, whereas in the dilute benzene solution, chiral information of the pendants that covalently bonded to the copolymer backbone was hardly transformed into a polymer backbone ( Figure 2C, inset).…”
Section: Amplification Of Macromolecular Helicity In Poly(phenylacetymentioning
confidence: 99%
See 1 more Smart Citation
“…If the solution contains enantiomeric or diastereomeric right-and left-handed helices, q c also depends on the excess of the one helical sense. 15,16,18 Under the constant copolymer concentration of 15 wt% in benzene at B25 1C, the q c value of poly(1L m -co-1D n ) was found to increase with the increasing percentage ee of the copolymer components, where a larger q c value means an increased preference of the one-handedness, and the copolymers with 30-50% ee of the components showed as large a q c value as that of the homopolymer poly-1L (100% ee; Figure 2C). This remarkable increase in the q c value against the percentage ee of the copolymers (positive nonlinear effect) indicated a significant amplification of the helical-sense excess in the LC state, whereas in the dilute benzene solution, chiral information of the pendants that covalently bonded to the copolymer backbone was hardly transformed into a polymer backbone ( Figure 2C, inset).…”
Section: Amplification Of Macromolecular Helicity In Poly(phenylacetymentioning
confidence: 99%
“…A similar, but non-covalent, hierarchical amplification of helical chirality was observed for a dynamic helical, charged poly(phenylacetylene) in water. [16][17][18] Recently, we have reported a unique amplification of macromolecular helicity of dynamic helical poly(phenylacetylene)s copolymers composed of optically active and achiral phenylacetylenes bearing L-alanine decyl esters (1L) and 2-aminoisobutylic acid decyl esters (Aib) as the pendant groups, respectively, (poly(1L m -co-Aib n )), in the cholesteric LC state and two-dimensional (2D) crystals on substrate. 19 Mesoscopic cholesteric twist (cholesteric helical pitch) in the LC state of the copolymers in concentrated solutions and high-resolution atomic force microscopy (AFM) images of the self-assembled 2D helix bundles of the copolymer chains on substrate enabled us to determine the helical-sense excesses of the copolymers, leading to a conclusion that the macromolecular helicity of poly(1L m -co-Aib n )s was hierarchically amplified in the order of the dilute solution, in LC state and 2D crystal (sergeants and soldiers effect).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the X-ray analysis of LC samples, the most plausible helical structure of 18-HCl is proposed to be a 23/10 helix ( Figure 3). 55 An optically active helical poly(phenylacetylene) bearing an L-alanine (L-Ala) residue with a long n-decyl chain as pendants (L-19) was found to exhibit an exceptionally long q-value of B130 nm in nonpolar solvents, such as CCl 4 , benzene and toluene. Interestingly, its q-value dramatically decreased to 19-43 nm in polar solvents, such as tetrahydrofuran and chloroform ( Figure 4).…”
Section: Helical Structure Determination Of Liquid Crystalline Helicamentioning
confidence: 99%
“…Meanwhile, Nagai et al 54 also reported a typical stepwise chiral amplification process induced by a chiral dopant. Taking advantage of the clear changes in the CD spectra and the macroscopic cholesteric twist in the LC state, this hierarchically chiral amplification system could be used to detect small amounts of chiral molecules.…”
Section: Chiral Interaction-induced Morphological Changes In Smart Pomentioning
confidence: 99%